DESCRIPTION OF KNOWLEDGE AND ATTITUDE OF CHICKEN NUMBER TRADERS ON RHODAMIN B CONTENT IN TOMATO SAUCE: (Case Study in Gubeng District, Surabaya in 2021) - SASKIYYAH CITRA TUNGGA DEWI; Marlik; Putri Arida Ipmawati (Jurnal Hygiene Sanitasi, 2021)
Food coloring is a food additive that can improve or give color to food. Currently, there are still foods with prohibited synthetic dyes, namely Rhodamin B. Based on a preliminary study conducted in November 2020 in Gubeng District, it was found that chicken noodle traders were using tomato sauce with physical characteristics containing Rhodamin B such as striking red and inhomogeneous colors. . The purpose of this study was to identify the content of Rhodamin B in tomato sauce and to assess the knowledge and attitudes of chicken noodle traders regarding Rhodamin B dye in tomato sauce in the Gubeng District. This type of research is descriptive by using approach cross sectional. The sample in this study was tomato sauce from chicken noodle traders. The sampling technique for tomato sauce is total samplingsampling and thetechnique for chicken noodle traders is proportional random sampling. Data analysis was described descriptively from the results of laboratory examinations and questionnaire sheets and then grouped or classified. The results showed that the tomato sauce brand "A" was positive for Rhodamin B, the knowledge of chicken noodle traders about Rhodamine B dye in tomato sauce was sufficient (56.8%) and the attitude of the traders was mostly sufficient (59.1%). The conclusion of this study is that brand "A" tomato sauce contains Rhodamine B positive, the knowledge and attitude of chicken noodle traders about Rhodamine B dye in tomato sauce is sufficient. It is better for people, especially chicken noodle traders, to be more careful before buying tomato sauce.